Reseñas - Felisa Bermejo Calleja; Laura Mariottini; Clara Elena Prieto Entrialgo; Renata Londero; Elena Landone; Rosana Ariolfo; Sara Polverini (Cuadernos AISPI, 2016)
Florencio del Barrio de la Rosa, Ejercicios de lexicología del español, Muenchen, Lincom, 2014, 191 pp. ISBN 9783862885572